Phase II study of everolimus in children and adults with neurofibromatosis type 2 and progressive vestibular schwannomas. Issue 2 (4th December 2013) - Karajannis, Matthias A.; Legault, Geneviève; Hagiwara, Mari; Giancotti, Filippo G.; Filatov, Alexander; Derman, Anna; Hochman, Tsivia; Goldberg, Judith D.; Vega, Emilio; Wisoff, Jeffrey H.; Golfinos, John G.; Merkelson, Amanda; et al.
Abstract: Background: Activation of the mammalian target of rapamycin (mTOR) signaling pathway is thought to be a key driver of tumor growth in Merlin ( NF2 )-deficient tumors. Everolimus is an oral inhibitor of mTOR complex 1 (mTORC1) with antitumor activity in a variety of cancers. Methods: We conducted a single-institution, prospective, 2-stage, open-label phase II study to estimate the response rate to everolimus in neurofibromatosis type 2 (NF2) patients with progressive vestibular schwannoma (VS). Ten eligible patients were enrolled, including 2 pediatric patients. Everolimus was administered at a daily dose of 10 mg (adults) or 5 mg/m 2 /day (children <18 y) orally in continuous 28-day courses, for up to 12 courses. Response was assessed every 3 months with MRI, using 3-dimensional volumetric tumor analysis, and audiograms. Nine patients were evaluable for the primary response, defined as ≥15% decrease in VS volume. Hearing response was evaluable as a secondary endpoint in 8 patients. Results: None of the 9 patients with evaluable disease experienced a clinical or MRI response. No objective imaging or hearing responses were observed in stage 1 of the trial, and the study was closed according to predefined stopping rules. Conclusion: Everolimus is ineffective for the treatment of progressive VS in NF2 patients. We are currently conducting a pharmacokinetic/pharmacodynamic ("phase 0") study of everolimus in presurgical VS patients to elucidate the biological basis for apparent treatment resistance to mTORC1 inhibition in these tumors.